Gratitude among advanced cancer patients and their caregivers: The role of early palliative care - Borelli, Eleonora; Bigi, Sarah; Potenza, Leonardo; Gilioli, Fabio; Artioli, Fabrizio; Porzio, Giampiero; Porro, Carlo Adolfo; Efficace, Fabio; Bruera, Eduardo; Luppi, Mario; Bandieri, Elena (Frontiers in Oncology, 2022)
Objective A cancer diagnosis represents a unique trauma, given its life-threatening, multidimensional, and uncertain nature. Gratitude is a construct representing the emotional state that arises when individuals recognize that a benefit has been received as a result of someone else’s action or a spiritual entity’s intervention. Based on the positive psychological wellbeing, gratitude has been associated with improved health outcomes even in the disease setting. Thus, the models of care that foster gratitude should be adopted in the clinical context. This study aims to explore whether and how gratitude may originate in patients with advanced cancer and their caregivers undergoing early palliative care (EPC). Methods We analyzed 251 reports from 133 patients and 118 caregivers describing their clinical experience in two EPC units. The sources of gratitude were identified and ranked based on their frequencies. Words expressing gratitude and words referring to communication and spirituality were collected by means of the Linguistic Inquiry and Word Count software and correlated. Results In total, 123 (92.5%) of 133 patients’ and 97 (82.2%) of 118 caregivers’ reports, respectively, included explicit or implicit expressions of gratitude. Gratitude was associated specifically with successful physical symptom management, emotional support, improved attitude toward death, better information, humanity, and the familiar environment. The use of words of gratitude in patients’ reports was positively correlated with the use of words referring to communication (r = .215, p = .026) and spirituality (r = .612, p <.001). Conclusion Our results suggest that interventions within the EPC model based on doctor–patient–caregiver communication may allow patients and caregivers to experience a feeling of gratitude, and this may represent a resource to be exploited to improve their physical and psychosocial wellbeing.